Desain Kurikulum Pembelajaran Bahasa Arab Kontemporer - Mohammad Syah Rizal Niqie; Nur Ahid (Universitas Islam Tribakti Lirboyo Kediri, 2023)
The Arabic language learning curriculum plays a very important role in the development of Arabic competence in learners. An effective and structured design of this curriculum can facilitate a continuous learning process, provide clear guidelines for instructors and students, and promote the attainment of desired learning goals. This paper describes several important aspects that need to be considered in the design of an Arabic learning curriculum. The several aspects that must be considered in the design of learning curriculum are curriculum design as a scientific discipline, student-oriented curriculum design, community-oriented curriculum design, and technological curriculum design. After knowing some of the aspects above, it will then be described how the design of the Arabic learning curriculum is applied. The research method used is to use qualitative descriptive technique procedures, namely research using qualitative data and then describing it to be able to produce a clear, precise and detailed description of a case studied in this case regarding the design of the Arabic language learning curriculum. The results obtained from this paper are Arabic learning curriculum design using curriculum design as a scientific discipline, student-oriented curriculum design, community-oriented curriculum design, technological curriculum design as long as it still includes 4 students' Arabic proficiency, namely listening ability, ability speaking, reading ability, and writing ability.